IMPLEMENTASI SISTEM ANTRIAN DIGITAL DI KANTOR KECAMATAN WINONGAN KABUPATEN PASURUAN - Satunggale Kurniawan; Rusmini Rusmini; Muhammad Afifi Rahman (PT. Jurnal Center Indonesia Publisher, 2024)
This research aims to uncover the problems of Integrated Services (PATENT) in the Winongan District Office, Pasuruan Regency with a MANUAL queuing system. From some information gathered from people queuing, services using a manual queuing system are less effective and efficient. So, to meet the needs of good community service, District Offices need to innovate a DIGITAL queuing system. Integrated Service (PATENT) problems at the Winongan District Office, Pasuruan Regency with a MANUAL queuing system. From some information gathered from people queuing, services using a manual queuing system are less effective and efficient. So, to meet the needs of good community service, District Office Agencies need to innovate a DIGITAL queuing system. Innovation is a shift from traditional management principles, processes and practices or a shift from old organizational forms to modern management. Government services to the community, known as public services, are a very strategic issue because of the interaction between the government and the community. This research uses a qualitative descriptive approach to determine public service innovation. The data used are primary data and secondary data. Data collection techniques were carried out using observation, interviews and documentation. The research results show that public service innovation with a digital queuing system is a conceptual innovation which gives rise to new paradigms, ideas, thinking and breakthroughs. Meanwhile, delivery innovation includes new ways or ways of solving problems, providing services or interacting with clients for the purpose of providing special services to customers.